Traces of Pre-Greek Linguistics Substratum in Early Byzantine Toponymy: Lists Related to Macedonia and Thessaly in Procopius’ "Buildings" - Kuzmanovska, Jasminka (Studia Ceranea, 2023)
In our contribution, we will focus on the traces of the old Pre-Greek linguistics substratum in certain names of forts from Justinian’s building program presented in the Procopius’ Buildings (Περὶ κτισμάτων, De aedificiis). Actually, the Book IV of the panegyric features a description of fortifications, built and restored by the Emperor Justinian in the European territories. This is the most detailed book in the work, written with great care and completeness, most likely due to the fact that the danger of barbarian incursions in these areas was the greatest. In the paper we will present certain examples of place names which obviously contain remnants of relict languages as very important and valuable toponomastic evidence, typical for the broader area. We are going to inspect the etymology of the place names by Procopius attested as Λάρισσα, Γόμφοι, Λόσσονος, Πέλεκον, Χάραδρος and Βάβας. If possible, we will comparatively examine testimonies from other ancient and medieval sources, as well as epigraphic and archeological data for each name.